Role of rap1B and p21ras GTPase-activating protein in the regulation of phospholipase C-gamma 1 in human platelets. - Torti, M (1992)
Thrombin activates phospholipase C in human platelets, but the specific isoenzymes activated and the signal pathway used are unknown. Using specific antibodies, we found that phospholipase C-gamma 1 and the p21ras GTPase-activating protein, rasGAP, are present in human platelets. Furthermore, phospholipase C-gamma 1 was detectable, based on enzyme activity and Western blot analysis, in immunoprecipitates of rasGAP, suggesting that these two proteins form tight complexes. The pool of phospholipase C-gamma 1 associated with rasGAP was phosphorylated but not through tyrosine phosphorylation. Although thrombin stimulation had no effect on the level of phosphorylation of phospholipase C-gamma 1 and only slightly increased the tyrosine phosphorylation of rasGAP, the agonist induced the association of rasGAP with rap1B, as indicated by the appearance of rap1B on a Western blot of rasGAP immunoprecipitates. Our results suggest the formation of a signaling complex involving rasGAP, phospholipase C-gamma 1, and rap1B that might be important in the cascade leading to platelet activation.